Histochemical studies on the Coagulating Gland of Albino Rat (Rattus norvegicus) - Bindu, M.; Kishore, P. V.S.; Raju, N. K.B.; Nagamalleswari, Y.; Sreenu, Makkena (Indian Journal of Veterinary Anatomy, 2018)
The coagulating gland, the additional paired accessory sex gland in the rat, was compound tubular. The parenchyma consisted of the secretory units and the ducts lined by simple cuboidal or low columnar epithelium which projected into the lumen and formed folds inside the compartments. A weak PAS positive reaction was observed in the gland indicating the presence of little amount of carbohydrates. This reaction in all these regions became still weak upon treatment with saliva. A positive reaction for proteins was observed in the cytoplasm of the secretory cells and in the luminal fluid where the cells have discharged their secretion. No reaction for lipids was observed in the coagulating gland in any of the glandular components. A mild acid phosphatase activity was observed in the secretory cells located peripherally. A very weak alkaline phosphatase activity was observed towards the luminal side in the epithelial cells of the secretory units and in a few of the epithelial cells lining the ducts.